Pharmacokinetics Profile and Genetics of Double Antiviral Therapy with Remdesivir and Nirmatrelvir/Ritonavir for Prolonged COVID-19 in Patients Treated with Rituximab: A Real-Life Study and Literature Review - Ilaria De Benedetto; Silvia Corcione; Carlotta Giambra; Matteo Ferrante; Simone Mornese Pinna; Elisa Zanotto; Alice Palermiti; Francesca Sidoti; Luca Scaglione; Cecilia Grosso; Martina Billi; Tommaso Lupia; et al. (MDPI AG, 2024)
Introduction: Patients with hematologic malignancies are more likely to develop severe and prolonged SARS-CoV-2 infection, often showing viral persistence despite the use of authorized antivirals. Herein, we report the cases of four patients who received rituximab for different conditions and developed persistent COVID-19 treated with an extended course of dual antivirals, Nirmatrelvir/Ritonavir and Remdesivir. Moreover, we describe the pharmacokinetics and pharmacogenetics (PK/PG) characteristics of Nirmatrelvir/Ritonavir and Remdesivir treatment in two of these patients. Methods: Plasma specimens for evaluation of trough concentrations (Ctrough) were collected 10 min before the daily dose administration, in addition to 3 h (Cmax), 4 h (C4h), 6 h (C6h) and 1 h (Cmax) after the administration of Nirmatrelvir/Ritonavir and Remdesivir, respectively. The following gene single-nucleotide polymorphisms (SNPs) were investigated: ABCB1 3435 (rs1045642) C > T, ABCB1 1236 (rs1128503) C > T, PXR 63396 (rs2472667) T > C, CYP2D6 (rs1135840) G > C, and CYP3A4*1B (rs2740574) G > A. Results: Double antiviral treatment was successful in terms of symptoms resolution, whereas three out of four patients achieved microbiological eradication. Based on our results, concentrations of Nirmatrelvir ranging from 50 to 5000 ng/mL were effective, whereas a higher concentration (range 1068-3377 ng/mL), compared to that previously reported in patients with similar weight and BMI, was evidenced for Ritonavir. Considering the genetic variant analysis, ABCB1 3435 CT and 1236 CT genotypes were found in patient 1; and ABCB1 3435 CC and 1236 CC in patient 2. In conclusion, this real-life study supports the usefulness of TDM and genetics in immunocompromised patients with persistent SARS-CoV-2 infection, a challenging setting for clinicians in which personalized medicine may improve outcome.